What the snake leaves in its wake: Functional limitations and disabilities among snakebite victims in Ghanaian communities. - Leslie Mawuli Aglanu; John Humphrey Amuasi; Bob A Schut; Jonathan Steinhorst; Alexis Beyuo; Chrisantus Danaah Dari; Melvin Katey Agbogbatey; Emmanuel Steve Blankson; Damien Punguyire; David G Lalloo; Jörg Blessmann; Kabiru Mohammed Abass; et al. (Public Library of Science (PLoS), 2022)
Background The estimated five million snakebites per year are an important health problem that mainly affect rural poor populations. The global goal is to halve both mortality and morbidity from this neglected tropical disease by 2030. Data on snakebite morbidity are sparse and mainly obtained from hospital records. Methods This community-based study was conducted among 379 rural residents with or without a history of snakebite in the Ashanti and Upper West regions of Ghana. All participants in the snakebite group were bitten at least six months before the day of survey. The World Health Organisation Disability Assessment Schedule 2.0 (WHODAS 2.0) and the Buruli Ulcer Functional Limitation Score were used to obtain patient-reported measure of functioning and disability. Long-term consequences were evaluated based on the severity of the symptoms at the time of the snakebite. Findings The median (IQR) time since the snakebite was 8.0 (3.5-16.5) years. The relative risk of disability was 1.54 (95% CI, 1.17-2.03) in the snakebite group compared to the community controls. Among patients with clinical symptoms suggesting envenoming at the time of bite, 35% had mild/moderate disabilities compared to 20% in the control group. The disability domains mainly affected by snakebite envenoming were cognition level, mobility, life activities and participation in society. A combination of the severity of symptoms at the time of the bite, age, gender and region of residence most accurately predicted the odds of having functional limitations and disabilities. Conclusion The burden of snakebite in the community includes long-term disabilities of mild to moderate severity, which need to be considered when designing appropriate public health interventions. Estimating the total burden of snakebite is complicated by geographic differences in types of snakes and their clinical manifestations.